Queimadas e incêndios florestais no processo de transformação do uso e cobertura da terra na zona de influência da BR-163, no estado do Pará - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
The BR-163, a road axis in the Brazilian Amazon, had its construction implemented as a strategic part of a geopolitics focused on integration and occupation, with the insertion of agro-industrial activities and distribution to the market outside. The problem addressed here is the dynamics of occupation in the influence of the BR-163 that presents a change in the landscape based on the deforestation and the use of fire for land conversion. The purpose of this research was to identify the characteristics of the burning practice, the vectors to which it is associated company, in addition to proposing the mapping of the risk of fires and forests in the zone of influence of the BR-163 in the stretch between the municipalities of Trairão to Novo Progresso, in the State of Pará. The methodological procedures adopted depart from the bibliographic survey on the historical process of occupation of the Amazon, the expansion of productive activity and the multiple factors that form. The results obtained demonstrate how State policy was and still is essential in the dynamics of land use in the Amazon, especially in Pará, which, from a series of state plans, including the construction of the highway BR-163, and the creation of protected areas around it, has been highlighted over the years by the rates of deforestation and the practice of fires that endanger entire ecosystems. The risk mapping points out areas priorities for monitoring and inspection during the dry season, declaring hazard levels according to the selected variables, allowing verification of areas more vulnerable to the practice of burning in this region.
Keywords: Incêndios florestais - Pará; Queimada - Amazônia; Desmatamento - Amazônia; CIENCIAS HUMANAS; CIENCIAS HUMANAS: GEOGRAFIA; Queimadas; Incêndios florestais; Zona de Influência; BR-163; Pará